2008
DOI: 10.1152/jn.90691.2008
|View full text |Cite
|
Sign up to set email alerts
|

Selective, State-Dependent Activation of Somatostatin-Expressing Inhibitory Interneurons in Mouse Neocortex

Abstract: Fanselow EE, Richardson KA, Connors BW. Selective, statedependent activation of somatostatin-expressing inhibitory interneurons in mouse neocortex. J Neurophysiol 100: 2640 -2652, 2008. First published September 17, 2008 doi:10.1152/jn.90691.2008. The specific functions of subtypes of cortical inhibitory neurons are not well understood. This is due in part to a dearth of information about the behaviors of interneurons under conditions when the surrounding circuit is in an active state. We investigated the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
240
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(268 citation statements)
references
References 51 publications
26
240
2
Order By: Relevance
“…Our results demonstrate that SST signaling in neuronal cilia is critical for novelty detection. Cilia extruding into the extracellular space are coated with SST 3 , suggesting they are sensitive detectors of increases in SST levels such as would occur during high-frequency neuronal firing (Fanselow et al, 2008). Decreased SST levels found in hippocampus and cortex in Alzheimer's disease (Burgos-Ramos et al, 2008) could contribute to deficits in recognition memory in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that SST signaling in neuronal cilia is critical for novelty detection. Cilia extruding into the extracellular space are coated with SST 3 , suggesting they are sensitive detectors of increases in SST levels such as would occur during high-frequency neuronal firing (Fanselow et al, 2008). Decreased SST levels found in hippocampus and cortex in Alzheimer's disease (Burgos-Ramos et al, 2008) could contribute to deficits in recognition memory in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the aroused state, when acetylcholine levels are up, the increased feedforward thalamocortical excitation of layer 4 spiny neurons (and reduced feedforward inhibition) could be countered by this near simultaneous hyperpolarizing current. However, somatostatin-positive GABAergic interneurons are excited by cholinergic inputs (Fanselow et al, 2008) and provide an inhibitory synaptic drive onto fast-spike interneurons (Kisvárday et al, 1993;Hughes et al, 2000). Thus, activation of this class of GABAergic interneuron in the alert state would inhibit the SINs, while in the nonalert state they would be disinhibited.…”
Section: Possible Mechanisms Behind Thalamocortical Disengagementmentioning
confidence: 99%
“…The capability of the LTS cells to oscillate synchronously at around 10ϳ30 Hz has been indicated by calculating phase-response curves using the dynamic-clamp conductance injection technique (Mancilla et al 2007). Also, it has been shown that the somatostatin-positive cells can fire rhythmically at around 3ϳ10 Hz, often synchronously (Fanselow et al 2008) The short-term depressing synapse enhances the resonance by about a factor of two. C-E: schematic diagrams of the effect of firing patterns on downstream neurons.…”
Section: Discussionmentioning
confidence: 99%
“…LTS cells have been shown to form an electrically coupled network via specific gap junctions (Gibson et al 1999), which is distinct from the network of fast spiking (FS) cells, another class of GABAergic interneurons, which, in contrast, selectively targets pyramidal somata and proximal dendrites. Several studies (Fanselow and Connors 2010;Fanselow et al 2008;Mancilla et al 2007;Vierling-Claassen et al 2010) have suggested that LTS cells can fire in synchrony at relatively slow frequencies (5ϳ30 Hz, around the -to ␤-frequency ranges), presumably by virtue of electrical coupling, again in contrast to the FS cells, which typically show synchronized firing in the ␥-frequency range (30ϳ80 Hz) (Buszsaki 2006;Fries 2009;Gouwens et al 2010;Hasenstaub et al 2005;Kopell and Ermentrout 2004;Morita et al 2008;Tateno et al 2004;Tiesinga and Sejnowski 2009;Wang and Buzsaki 1996;Whittington and Traub 2003). Cholinergic agonists induce beta oscillations in superficial layers of prefrontal cortical slices, which are independent of rhythms in the deeper layers (van Aerde et al 2009).…”
mentioning
confidence: 99%